2020
DOI: 10.1016/j.artd.2020.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Modular Dual-Mobility Liner Malseating: A Radiographic Analysis

Abstract: Background: With dislocation as a leading cause for revision after total hip arthroplasty (THA), modular dualmobility (MDM) constructs are more commonly used at present in an attempt to decrease postoperative instability. With modularity, there is potential for additional complications, including malseating of the liner. The goal of this study was to perform a radiographic analysis on the incidence of MDM liner malseating. Methods: We retrospectively identified 305 patients (305 THAs) who underwent primary THA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The use of modDM implicates also the risk of modular metal liner malseating which is reported with an incidence up to 5.8%. Liner malseating may lead to increased fretting corrosion and metal related issues, component dissociation and reduced stability [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of modDM implicates also the risk of modular metal liner malseating which is reported with an incidence up to 5.8%. Liner malseating may lead to increased fretting corrosion and metal related issues, component dissociation and reduced stability [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some possible hypotheses include a prominent acetabular screw, and soft-tissue or bone interposition at the rim of the implant. 5 - 7 , 16 , 17 In addition, the Stryker modular dual mobility liner does not sit flush with the face of the acetabular shell, making it difficult to assess if the liner is completely seated circumferentially. Another proposed explanation is that the acetabular shell can deform upon impaction into hard bone, thus slightly altering its hemispherical shape.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques to reduce the risk of malseating should include thorough removal of all soft tissue and osteophytes around the periphery of the component that may impede seating of the liner and confirmation that any acetabular screws are well seated. Recently, Chalmers et al 17 found a 1.3% incidence of malseated implants in their patient cohort, and advocated using a four-quadrant test to mechanically verify proper implant engagement, particularly in the inferior segment which can be challenging to visualize intraoperatively. The four-quadrant test involves tapping the modular liner in all four quadrants using a liner impactor and assessing whether there is any movement or disengagement of the liner.…”
Section: Discussionmentioning
confidence: 99%
“…Use of modDM implicates also the risk of modular metal liner malseating which is reported with an incidence up to 5.8%. Liner malseating may lead to increased fretting corrosion and metal related issues, component dissociation and reduced stability [25,26].…”
Section: Discussionmentioning
confidence: 99%